Law models for one world - Anan, Ahmed Anany (AUC Knowledge Fountain, 2012)
The World Bank's prevailing conception that unifies the economic tools and the social goals of development in one comprehensive agenda through using law models in the core is unrealistic process that allows the Bank to play a political role regarding the policies of the member countries. The alternative strategy, in my view, is either to determine a point of reference to lead the development process of the transition countries instead of providing unified law models or to determine a specific legal reform agenda for each country that is compatible with its priorities and necessities. This alternative strategy should be limited to the mandate of the World Bank as a financial institution avoiding any extra burdens that contradict with the sovereignty of the member states. In fact, in my contention, the neoliberal comprehensive agenda of the World Bank may be described as a paternalistic assistance to the transitional countries that ignores the different goals of development for each country.